2014
DOI: 10.1002/tal.1201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of combined system of framed tube and shear walls by Galerkin method using B‐spline functions

Abstract: SUMMARYIn this article, dynamic parameters (natural frequencies and mode shapes) of tall buildings that consist of framed tube and shear walls are obtained using a simple approximate method. The three-dimensional structure is replaced by an equivalent cantilever beam, considering both bending and shear deformations. On the basis of dynamic equilibrium, the governing differential equation of motion is obtained and converted to its corresponding weak form. B-spline functions are then utilized to approximate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Therefore, if horizontal loadings are to be efficiently resisted, the appropriate structural form in a tall building should be determined (Kamgar and Saadatpour 2012). There are different structural forms of tall buildings and numerous researches have been carried out about the approximate and exact methods of investigating the behavior, deflection, vibration, optimal design and control of such buildings (Rahgozar et al 2015;Alavi et al 2018;Khatibinia et al 2018;Kamgar et al 2018). An effective technique to resist lateral loading in tall building is to use an outrigger-braced system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if horizontal loadings are to be efficiently resisted, the appropriate structural form in a tall building should be determined (Kamgar and Saadatpour 2012). There are different structural forms of tall buildings and numerous researches have been carried out about the approximate and exact methods of investigating the behavior, deflection, vibration, optimal design and control of such buildings (Rahgozar et al 2015;Alavi et al 2018;Khatibinia et al 2018;Kamgar et al 2018). An effective technique to resist lateral loading in tall building is to use an outrigger-braced system.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the deformed shape of the shear wall–frame structural system is the combination of flexural mode and shear mode. Rahgozar et al presented a dynamic analysis of combined system of framed tube and shear walls by Galerkin method using B‐spline functions. Kamgar et al determined the first natural frequency of tall buildings with a combined system of framed tube, shear core, belt truss, and outrigger system with multiple jumped discontinuities in the cross‐section of framed tube and shear core under axial force.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] This paper focuses on the numerical solution of two-dimensional (2D) elastodynamic problems by using a new and attractive method that is named weight-adaptive space-time discontinuous isogeometric analysis (WA-STDIGA). Before giving some additional explanations about the proposed approach, it is worthwhile to note that the IGA is a new powerful numerical method first proposed by Hughes et al 30 Dynamic and static analysis of plates and shells, [31][32][33][34][35] crack propagation analysis, 36,37 fluid mechanics, 38 and dynamic analysis of tall buildings 39 are only few samples where the IGA has been successfully used. In addition, in recent years, many articles have focused on the space-time formulation of IGA as an alternative method to space-time FEM.…”
Section: Introductionmentioning
confidence: 99%